2011
DOI: 10.1002/cncr.25891
|View full text |Cite
|
Sign up to set email alerts
|

Uterine serous papillary carcinomas overexpress human trophoblast‐cell‐surface marker (trop‐2) and are highly sensitive to immunotherapy with hRS7, a humanized anti‐trop‐2 monoclonal antibody

Abstract: BACKGROUND: Uterine serous papillary carcinoma (USPC) was an aggressive and chemotherapy resistant variant of endometrial cancer. The authors evaluated the expression of human trophoblast-cell-surface-marker (Trop-2) and the potential of hRS7, a humanized anti-Trop-2 monoclonal antibody, as a novel therapeutic strategy against USPC. METHODS: Trop-2 expression was evaluated by immunohistochemistry (IHC) in a total of 23 USPC. Six primary USPC cell lines were assessed by flow cytometry and real-time polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 31 publications
(60 reference statements)
3
43
0
Order By: Relevance
“…18 Although the relationship between high Trop-2 expression and aggressiveness of epithelial neoplasms remains unclear, it has been suggested that Trop-2, possessing cytoplasmic serine and tyrosine phosphorylation sites, might function as a cell signal transducer and regulator of tumor cell growth and increase tumor cell resistance to apoptosis. 19 Consistent with this view, Guerra et al 20 have shown that a large fraction of human cancers express a bicistronic CYCLIN D1-TROP2 mRNA chimera, acting as an oncogene able to induce aggressive tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Although the relationship between high Trop-2 expression and aggressiveness of epithelial neoplasms remains unclear, it has been suggested that Trop-2, possessing cytoplasmic serine and tyrosine phosphorylation sites, might function as a cell signal transducer and regulator of tumor cell growth and increase tumor cell resistance to apoptosis. 19 Consistent with this view, Guerra et al 20 have shown that a large fraction of human cancers express a bicistronic CYCLIN D1-TROP2 mRNA chimera, acting as an oncogene able to induce aggressive tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…18 Tumors were staged according to the International Federation of Gynecologists and Obstetricians' 2010 operative staging system. Source-patient characteristics of these 3 poorly differentiated EEC cell lines (EEC-ARK-1, EEC-ARK-2, and EEC-ARK-3) are described in Table 1.…”
Section: Establishment Of Grade 3 Eec Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47][48] ABBREVIATIONS AIRE, autoimmune regulator; CREB, cyclic AMP-responsive-element binding protein; FOXM1, forkhead box M1; Get, Grainyhead-like Abbreviations: ERa, oestrogen receptor a; (C), cytoplasmic staining; (N), nuclear staining; PgR, progesterone receptor; Rho, Spearman's correlation coefficient; P, two-tailed P-value. Significant correlations are highlighted (grey shading).…”
mentioning
confidence: 99%
“…The cell-surface markers overexpressed in EC are the tight junction proteins, like claudin-3 and claudin-4, highly expressed in endometrioid, serous papillary, and clear-cell EC, the folate receptor a, a membrane-bound molecule, and the mesothelin, a glycosylphosphatidylinositol-linked cell-surface antigen; all of them are upregulated more frequently in serous than in endometrioid EC. The trophoblast cell-surface marker (Trop-2) is a cell-surface glycoprotein, which is highly expressed in both types of [45] EC, while epithelial cell adhesion molecule, a reliable marker for tumor-initiating cells, and L1 cell adhesion molecule (L1CAM), a key driver for tumor cell invasion and EMT, are highly expressed among serous EC [46,47].…”
Section: Scientific Rationalementioning
confidence: 99%